Factors associated with rates of gestational weight gain among pregnant women in Batu Pahat district of Johor state, Malaysia - Woon, Fui Chee; Yu, Min Si; Chin, Yit Siew (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: This cross-sectional study determines factors associated with the rates of gestational weight gain (GWG) among women in the second and third trimester of pregnancy. Methods: A total of 180 pregnant women (29.2 ± 4.3 years old) attending the maternal and child health clinics in Batu Pahat district were enrolled in the present study be-tween January and February, 2015. Information regarding demographic characteristics, obstetrical history, physical activity, and calorie intake was assessed through direct interview. Anthropometric data were collected from medical records. GWG rates were determined based on 2009 IOM recommendations. Results: Of the 180 pregnant women, 37.2% were at their second trimester and 62.8% were at the third trimester of pregnancy. While 53.3% of them had excessive GWG rate, 28.9% have inadequate GWG rate. More than half of the women (56.7%) were normal weight, 21.1% overweight, 14.4% underweight, and 7.8% obese before pregnant. The total mean activity and energy intake of the pregnant women were 195.9±94.2 MET-hour/week and 2365±709 kcal/day, respectively. The multinomial logistic model indicates that women who were overweight or obese at pre-pregnancy were seven times more likely to have excessive GWG rate (OR = 7.44, 95% CI = 2.07-26.66) as compared to women who were pre-pregnancy normal weight. Conclusions: About four in every five of the pregnant women had their GWG rates outside the IOM recommendations. Women who were overweight/obese at pre-pregnancy were at-risk of having excessive GWG rate, which underlines the importance of targeting these women for pre-conception counselling on GWG.